(untitled) (Journal of Economic Research & Business Administration, 2015)
In article the role of the human capital for successful innovative development of economy and a problem of financing in the conditions of integration into world space is considered. Investments into the person are the reliable guarantee of prosperity of the country as it is the investment into the future.